Skin manifestation of angioimmunoblastic T-cell lymphoma mimicking Hansen’s disease on histology - Shukla, Anju; Dabadghao, Sunil Sharad; Gupta, Surbhi; Jain, Priyanka (International Journal of Research in Dermatology, 2020)
Angioimmunoblastic T-cell lymphoma (AITL) is an uncommon form of peripheral T-cell lymphoma now put under the category of nodal T-cell lymphoma with follicular T helper phenotype. 50% cases of AITL have varied cutaneous manifestations including macules, papules, petechiae, purpura, nodules, non-specific rash and urticaria. Herein we present a case of AITL initially presented as maculopapular rash which on histology was mimicking as Hansen’s disease with perineural and perivascular inflammation; however, an infective organism could not be demonstrated. Later on, a delayed diagnosis was made on lymph node biopsy and immunohistochemistry and patient responded well with chemotherapy.